Intestinal permeability, vitamin A absorption and serum alpha-tocopherol in gastrointestinal stromal tumor patients treated with imatinib - Melichar, Bohuslav; Kašparová, Markéta; Kalábová, Hana; Dvorák, Josef; Hyšpler, Radomír; Tichá, Alena; Krcmová, Lenka; Plíšek, Jiří; Holecková, Petra; Solichová, Dagmar (Journal of nutritional science and vitaminology, 2010)
Administration of imatinib is the therapy of choice in patients with advanced (inoperable) or metastatic gastrointestinal stromal tumors (GIST). Gastrointestinal toxicity is one of the most common side effects of anticancer therapy, including imatinib. Measurement of intestinal permeability represents a method of noninvasive laboratory assessment of gastrointestinal toxicity. We have measured intestinal permeability (by determining absorption of lactulose, mannitol and xylose), vitamin A absorption and serum alpha-tocopherol in 16 patients with advanced/metastatic GIST treated with imatinib. Lactulose/mannitol and lactulose/xylose ratios as well as parameters of vitamin A absorption did not change significantly during the treatment, but a significant decrease of alpha-tocopherol was observed. We conclude that, in contrast to most other anticancer agents studied so far, imatinib does not have an effect on intestinal permeability. No effect on vitamin A absorption was observed, but serum alpha-tocopherol decreased significantly during the treatment.
Keywords: imatinib mesylát; Dietary Sucrose; permeabilita; Male; Vitamin A; protinádorové látky; Piperazines; alpha-Tocopherol; vitamin A; piperaziny; benzamidy; Adult; Pyrimidines; střevní sliznice; intestinální absorpce; dospělí; alfa-tokoferol; mužské pohlaví; senioři; Aged; gastrointestinální stromální tumory; Benzamides; Permeability; senioři nad 80 let; konzumní sacharóza; lidé; ženské pohlaví; Humans; pyrimidiny; Intestinal Mucosa; Aged, 80 and over; Intestinal Absorption; Female; lidé středního věku; Gastrointestinal Stromal Tumors; Antineoplastic Agents; Middle Aged; Imatinib Mesylate